Analisis Pola Kalimat Majemuk Bertingkat pada Karya Ilmiah dalam Buku Cerdas Cergas Berbahasa dan Bersastra Indonesia SMA/SMK Kelas XI Kurikulum Merdeka (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
In the paragraphs of scientific writings, it is possible to find multilevel compound sentences, namely sentences consisting of one basic sentence that acts as the core and one or many other basic sentences that also act as subordinate clauses. Thus, the writing team was moved to carry out an analysis of multilevel compound sentences. The purpose of this analysis is to examine or dissect multilevel compound sentences, both in the use of variations in patterns and sequences of clauses and their descriptions. A qualitative, descriptive approach is the method used in this analysis. The data used in this analysis comes from scientific papers entitled "Status Kondisi Terumbu Karang di Teluk Ambon" and "Karakteristik Vegetasi Habitat Orang Utan (Pongo pymaeus morio) di Hutan Tepi Sungai Menamang, Kalimantan Timur" in the Language and Literature Smart Book Indonesia SMA/SMK Class XI Independent Curriculum. This data was collected using observing and note-taking techniques. The results of this analysis indicate that there are 8 multilevel compound sentence forms, consisting of 6 multilevel compound sentences with time relations, 2 multilevel compound sentences with conditional relations, 2 multilevel compound sentences with comparative relations, 7 compound multilevel sentences with causal relations, 12 multilevel compound sentences with causal relations, 8 multilevel compound sentences with manner relations, 6 compound multilevel sentences with explanatory relations, and 16 compound multilevel sentences with attribute relations. This research is expected to be useful in providing an understanding of multilevel compound sentence patterns and can be used as reference material for subsequent research.